Acute non-puerperal uterine inversion ascribed to malignant mixed Mullerian tumor of uterus: a rare presentation. (28th May 2022) - Khoiwal, Kavita; Zaman, Rabia; Gill, Poonam; Joshi, Prashant; Gaurav, Amrita; Chaturvedi, Jaya
ABSTRACT: Non-puerperal uterine inversion is an extremely uncommon condition, and its occurrence due to malignant mixed Mullerian tumor (MMMT) of the uterus is quite exceptional. We report one such case of acute non-puerperal uterine inversion ascribed to MMMT in a 77-year-old postmenopausal woman. Such a case poses a diagnostic and management dilemma, and prior knowledge may result in a successful outcome.